Supplementing feedlot steers and heifers with Zilmax increases proportions of strip loin, chuck clod, and top sirloin steaks exceeding Warner-Bratzler shear force thresholds, whereas aging moderates this effect - Claus, H.C.; Brooks, J.C.; Shook, J.; Hilton, G.G.; Lawrence, T.E.; Mehaffey, J.M.; Johnson, B.J.; Allen, Dell M.; Streeter, M.N.; Nichols, W.T.; Hutcheson, J.P.; Yates, D.A.; et al. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Ractopamine hydrochloride (Elanco, Greenfield, IN) and Zilmax (zilpaterol hydrochloride; Intervet/Schering-Plough, Millsboro, DE) are β-adrenergic agonists approved in the United States and several other countries to increase growth rate, improve efficiency of feed utilization, and increase carcass meat yield. Zilmax has been shown to improve feed efficiency by 26% and increase hot carcass weight, longissimus muscle area, and meat yield. However, a few studies have shown that Zilmax significantly increased Warner-Bratzler shear force values (decreased tenderness). The objectives of our research were to determine the effects of supplementing feedlot diets of steers and heifers with Zilmax for 0, 20, 30, or 40 days before harvest and the subsequent effects of 7, 14, and 21 days of aging on tenderness of steer and heifer Longissimus lumborum (from strip loins) and heifer Triceps brachii (from chuck clods) and Gluteus medius (from top sirloin butts) muscles.
Keywords: Beef; Steers; Heifers; Zilmax; Warner-Bratzler shear force